Building Civilization in the Era of Science-Based Globalization & Da'wah - Mujiadi Mujiadi (CV. Syntax Corporation Indonesia, 2023)
History has been a witness, that the existence and absence of knowledge became the benchmark for the glory and fall of a nation. Science is the light of man, the light of his intellect, the generator of civilization, the bringer of happiness. But science doesn't come by itself. It must be sought, studied, pursued, lived and practiced as well as accounted for truthfully. This is the basis for building civilization, namely by making science the largest part of building a civilization. The development and change of an era is a characteristic of the development of human life from one side because of science and education. However, to become a civilization, of course, ethical aspects and noble morals must be conditions that greatly affect the progress of a society. This paper was prepared by utilizing library facilities as a means for collecting primary and secondary source data. The preparation procedure goes through four stages that must be fulfilled in conducting research, namely heuristics, criticism, interpretation, and historiography. The data sources used are written sources which include books, journals and internet sources. The culture of science is an initial prerequisite and an important thing for the glory of a person and a nation. An individual or a nation that has power or wealth that is not maintained let alone developed without a good culture of knowledge, then later he will depend on other people or nations who are more knowledgeable. Speaking of science, of course the concept of science in Islam is different from the concept of science understood in the Western view. So that errors in understanding the concept of science can cause differences in perception of science. The destruction of Western civilization is obviously very dangerous for human survival. Westernization or liberalization becomes a disease for civilization. So the solution to the salvation of human civilization is to jump-start Islamic civilization. A civilization built with the concept of science in Islam. Building a civilization based on science must be an Islamic intellectual tradition, in fact science is the foundation of the structure of the concept of building Islamic civilization. The continuity of this intellectual or scientific tradition cannot be separated from the contribution of scholars in the past in preserving and spreading these sciences. Their contribution to Islamic science actually began since the Prophet Muhammad SAW received a revelation, which was then conveyed to the Companions, so that the revelation conveyed contained the foundations of pure Islamic scholarship.